2014
DOI: 10.1139/cjpp-2014-0281
|View full text |Cite
|
Sign up to set email alerts
|

Anti-depressant effect of hesperidin in diabetic rats

Abstract: This study aimed to investigate the anti-depressant effect of hesperidin (Hsp) in streptozotocin (STZ)-induced diabetic rats. Additionally, the effect of Hsp on hyperglycaemia, oxidative stress, inflammation, brain-derived neurotrophic factor (BDNF), and brain monoamines in diabetic rats was also assessed. The Wistar rats in the experimental groups were rendered hyperglycaemic with a single dose of STZ (52.5 mg·(kg body mass)(-1), by intraperitoneal injection). The normal group received the vehicle only. Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…It has been extensively studied for its biological activities including antioxidant, anti-inflammatory, antihypercholesterolemic, and anticarcinogenic properties [17,[22][23][24][25]. The antioxidant activity of hesperidin has been used to protect against various types of insults such as cisplatin-induced acute renal injury [ 26], benzopyrene-induced lung carcinogenesis [27], 6hydroxydopamine-induced Parkinson's disease [28], and depressant in streptozotocin-induced diabetic rats [29]. In the present study, we found that hesperidin pretreatment significantly attenuated hepatic lipid peroxidation and GSH depletion in rats administered with INH plus RFP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively studied for its biological activities including antioxidant, anti-inflammatory, antihypercholesterolemic, and anticarcinogenic properties [17,[22][23][24][25]. The antioxidant activity of hesperidin has been used to protect against various types of insults such as cisplatin-induced acute renal injury [ 26], benzopyrene-induced lung carcinogenesis [27], 6hydroxydopamine-induced Parkinson's disease [28], and depressant in streptozotocin-induced diabetic rats [29]. In the present study, we found that hesperidin pretreatment significantly attenuated hepatic lipid peroxidation and GSH depletion in rats administered with INH plus RFP.…”
Section: Discussionmentioning
confidence: 99%
“…125 Antidepressant property of hesperidin was displayed by inhibiting L-arginine/ nitric oxide/ cyclic-GMP pathway and by elevating levels of BDNF in the brain, specifically in hippocampus. 126,127 A study showed antidepressant action of vitexin which was mediated through heightened levels of catecholamines (dopamine, adrenaline and noradrenaline) in the synaptic cleft and by interacting with dopaminergic, serotonergic and noradrenergic receptors. 128 Other flavonids including fisetin, 129 quercetin, 130 naringenin, 131,132 nobiletin (a dietary flavonoid), 133 luteolin 134 and kaempferitrin 135 also have reported antidepressant activity.…”
Section: Anti-depressantmentioning
confidence: 99%
“…[216][217][218][219][220] This compound is highly bioavailable in lemon fruits and their juices. The lower bioavailability of those compounds through oral delivery leads to lower beneficial effects at higher doses.…”
Section: Nano-hesperidinmentioning
confidence: 99%